THE SECOND MILLENNIUM: A PERSPECTIVE FROM THE BAHA’I FAITH - Merchant, A K (Journal of Dharma, 2001)
Our planet in its present form is several millions years old. To put it in perspective, visualize the human species a million years ago as composed of something like 100.000 inquisitive furry creatures living in the most fertile parts of Africa, Asia and perhaps Europe. There was land enough for the average family to occupy an expanse three times the size of Delhi city all by itself. But naturally most of them gravitated into the valleys favoured with the best water and game, leaving other regions almost empty. They did not live in villages though (for villages had not been invented) but rather roamed about in small groups hunting meat and gathering vegetables to feed themselves. If there was any religion at this point of time it was largely to do with the understanding of the mighty forces of Nature.